Correction: Chemical synthesis of human trefoil factor 1 (TFF1) and its homodimer provides novel insights into their mechanisms of action. Issue 51 (17th June 2020) - Braga Emidio, Nayara; Baik, Hayeon; Lee, David; Stürmer, René; Heuer, Jörn; Elliott, Alysha G.; Blaskovich, Mark A. T.; Haupenthal, Katharina; Tegtmeyer, Nicole; Hoffmann, Werner; Schroeder, Christina I.; Muttenthaler, Markus
Abstract : Correction for 'Chemical synthesis of human trefoil factor 1 (TFF1) and its homodimer provides novel insights into their mechanisms of action' by Nayara Braga Emidio et al., Chem. Commun., 2020, DOI: ; 10.1039/D0CC02321C .